Investigations on the microstructure and mechanical properties of dissimilar welds of inconel 718 and sulphur rich martensitic stainless steel, AISI 416. (April 2018) - Dev, Sidharth; Ramkumar, K. Devendranath; Arivazhagan, N.; Rajendran, R.
Graphical abstract: Highlights: Pulsed current gas tungsten arc welding of Ti stabilized stainless steel using Nb rich and Nb free fillers. Formation of Skeletal, Vermicular delta ferrite in the fusion zone of ER347 and Laves phase in ERNiCrMo-3 welds. Improved microstructure with minimal segregation in ERNiCrMo-4 welds. Pensive discussion on mechanical integrity of the weldments. Abstract: Turbine blisk and shaft assembly in aero-engines make use of dissimilar joints of Inconel 718 and martensitic stainless steel, AISI 416. The joining of these 5 mm thick aerospace alloys carried out by adopting current pulsing in Gas Tungsten Arc Welding (GTAW) has been addressed. Two Nb free consumables namely ERNiCrMo-4, ERNiCu-7 and a duplex filler ER2553 were used to join these dissimilar combinations. The weldments were systematically characterized using optical microscopy (OM) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDS). It is endorsed from the studies that the welds obtained from these fillers were free from deleterious Laves phase. Irrespective of fillers, the tensile failures were experienced at the base metal side of AISI 416. Room temperature Charpy V-notch impact test indicated that the weld joints employing ERNiCu-7 witnessed better impact toughness than other weldments. This study is highly in demand in aerospace industries and successfully addressed the choice of fillers in supressing the Laves phase.